Comparison of Elias Delta and Interpolative Coding Algorithms in Video File Compression - Khairani, Nani; Aripin, Soeb; Siagian, Meryance Viorentina (The IJICS (International Journal of Informatics and Computer Science), 2025)
Large video file sizes can burden storage capacity and slow down data transmission, making effective compression methods essential. WebM, a commonly used video format supported by platforms such as YouTube and Skype, often results in large file sizes that demand storage efficiency. This study compares two lossless compression algorithms—Elias Delta Code and Interpolative Coding—for compressing WebM video files. Interpolative Coding applies a non-linear approach based on the entire content of the message, while Elias Delta Code is an integer-based algorithm efficient for encoding positive numbers. This research is motivated by the lack of direct comparative studies between these two algorithms in the context of video compression. The objective is to evaluate their performance based on compression ratio, processing time, and storage efficiency. The results are expected to provide recommendations on the most suitable compression algorithm for high-complexity video files.